An improved free-field cross-talk cancellation method based on the spherical head model. (August 2017) - Xu, Huaxing; Xia, Risheng; Li, Junfeng; Yan, Yonghong
Abstract: Cross-talk cancellation (CTC) plays an important role in a 3-D audio system with loudspeakers reproduction. For designing the CTC filter coefficients, the transfer functions between the loudspeakers and the listener's ears are need to be determined in advance. Ideally, the individualized head-related transfer function (HRTF) is preferred. It provides a good performance but impractical for everyone, also with high load of computation due to convolution with a long order. Alternatively, the free-field transfer function is also frequently used because of its simplicity, especially for real-time application. However, in the absence of considering the listener's head effects, its performance is limited. In this paper, based on the spherical head model, an attenuation factor and a phase difference factor characterizing the head effects are integrated to the free-field CTC method. The proposed CTC method shows better performance than the free-field CTC method and has also less computational cost than the HRTF-based CTC method with a comparable performance.